PENGARUH STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN COFFE TOFFE JATIM EXPO SURABAYA - OCTAVIANI, ACHIRUL (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
Coffee shop business in Indonesia since the 2000s, which is where it presence is not only to satisfy functional requirements but it leads to emotional needs. People tend to relax and enjoy a coffee with because it requires not just a coffee. This is the impact of changes in people’s lifestyles are influenced by the culture of western society. It is also supported by a statement from the Association of Indonesian Food and Beverages (Gapmmi) targeting the food and beverage industry grew 8% to 10% in 2012. Owner of Coffe Toffe, that people in Surabaya have started requiring coffee not only to the need for coffee, but also the need to socialize while at the coffee shop. For this reason in 2006 Coffe Toffe began to open its first outlet in Surabaya. T test results obtained at 6,895 with a significance level less than 0.05, we conclude there is an influence of the Atmosphere Store Purchase Decision in Coffe Toffe Expo Surabaya East Java. Keyword: Store Atmosphere, Purchase Decision, cofffe shop